2008
DOI: 10.1016/j.cell.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Associating Protein Critical for Chromosome Attachment, Division, and Polar Organization in Caulobacter

Abstract: SUMMARY Cell polarization is an integral part of many unrelated bacterial processes. How intrinsic cell polarization is achieved is poorly understood. Here, we provide evidence that Caulobacter crescentus uses a multimeric pole-organizing factor (PopZ) that serves as a hub to concurrently achieve several polarizing functions. During chromosome segregation, polar PopZ captures the ParB•ori complex and thereby anchors sister chromosomes at opposite poles. This step is essential for stabilizing bipolar gradients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
474
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(506 citation statements)
references
References 42 publications
31
474
1
Order By: Relevance
“…39 and 40). This polar anchoring is required for effective chromosome segregation and cell division (39,40). Here, we showed that the orientation of the Caulobacter chromosome within the cell appears to be achieved by ''clocking'' the DNA molecule relative not to Cori but rather to parS.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…39 and 40). This polar anchoring is required for effective chromosome segregation and cell division (39,40). Here, we showed that the orientation of the Caulobacter chromosome within the cell appears to be achieved by ''clocking'' the DNA molecule relative not to Cori but rather to parS.…”
Section: Discussionmentioning
confidence: 85%
“…Clearly, there is a strong selective pressure for bacterial chromosomes to remain organized inside the cell, perhaps to coordinate DNA segregation with cell division. Indeed, RacA-mediated anchoring in B. subtilis prevents the formation of DNA-free forespores (41), and loss of polar parS/ParB anchoring in Caulobacter leads to defects in cell division (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The latter requirement may be due to the fact that chromosome II has many properties of a large plasmid and its Par proteins are more closely related to plasmid-encoded ones than to those encoded on chromosomes (22). In C. crescentus, the par system may be essential only indirectly, as it is used for proper localization of the cell division machinery through at least two other proteins, PopZ (6,13) and MipZ (53). PopZ captures the parB/ori complex and subsequently anchors it at opposite cell poles (6,13).…”
mentioning
confidence: 99%
“…In C. crescentus, the par system may be essential only indirectly, as it is used for proper localization of the cell division machinery through at least two other proteins, PopZ (6,13) and MipZ (53). PopZ captures the parB/ori complex and subsequently anchors it at opposite cell poles (6,13). This results in the FtsZ polymerization inhibitor MipZ, which also forms a complex with ParB, to localize to the poles.…”
mentioning
confidence: 99%
“…Polar protein complexes that interact with chromosome segregation factors have been identified in various bacteria, but the mechanistic consequences of these interactions have not been established (13)(14)(15). In Caulobacter, two distinct polar protein factors affect ParA-mediated centromere segregation: the new polespecific protein TipN (16,17) and the polar organizing protein PopZ (18,19). TipN is a large, membrane-anchored, coiledcoil rich protein that localizes to the new pole throughout the cell cycle and, in addition to roles in localization of flagellar synthesis (16,17), affects processive parS segregation via an unknown mechanism (6,20).…”
mentioning
confidence: 99%